LANGUAGE POLITENESS IN DIGITAL STREAMING: THE IMPLICATIONS TO EDUCATION AND ETHICS IN COMMUNICATIONS FOR THE TECHNOLOGICAL ERA - Mayrita, Hastari; Rahmawati, Shopia; Sholikhah, Hani Atus; Wongprakob, Wuttipong; Hidayat, Marzul; Fortunasari, Fortunasari; Masita, Ella; Marzulina, Lenny (LPPM Universitas Jambi, 2025)
This study investigates the phenomenon of politeness violations in digital live streaming interactions, focusing on gaming content on YouTube a platform increasingly characterized by the prevalence of “toxic” language, including harsh, derogatory, and provocative expressions. Such discourse poses a growing challenge to communication ethics and character education in the technological era. The research aims to analyze specific types of politeness principle violations and their implications for character formation and digital communication practices. Adopting a qualitative approach through observation, documentation, and interviews, the study found that violations most frequently targeted the principles of tact and generosity. Notably, these utterances were not merely spontaneous outbursts but deliberate strategies of performative impoliteness, designed to construct a particular self-image and amplified by platform algorithms seeking engagement. The novelty of this research lies in its integration of linguistic analysis, digital ethics, and character education within the context of real-time live streaming—a convergence rarely explored in prior studies. This interdisciplinary approach provides unique insights into how algorithm-driven platforms can normalize verbal aggression, influencing audience psychology and diminishing empathy values, particularly among student viewers. The findings highlight the urgent need to expand digital literacy education to encompass the ethical dimensions of communication, not just technical proficiency. The study recommends incorporating polite language awareness and ICT ethics into curricula to foster respectful, constructive interaction in online spaces.